2019
DOI: 10.1177/1937586719827946
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Light on Sleep and Sleep-Related Physiological Factors Among Patients in Healthcare Facilities: A Systematic Review

Abstract: Objectives: Lighting is one of the environmental factors which can improve patient sleep in healthcare environments. Due to the high degree of variation in study designs and results on this topic, the implications have been difficult to interpret. This review consolidates studies on the impact of bright light exposure on sleep to identify lighting conditions that can be applied and researched in future healthcare environments. Methods: We searched for peer-reviewed articles on the impact of light on sleep or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
(143 reference statements)
1
12
0
Order By: Relevance
“…Sleep Quality. Consistent with recent reviews [26,72,73], our meta-analysis revealed significant positive effects of USS using light therapy or acupuncture on TST night. Only light therapy was effective in improving SE and SoL, and decreasing the duration of awakenings, although the effects were small.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sleep Quality. Consistent with recent reviews [26,72,73], our meta-analysis revealed significant positive effects of USS using light therapy or acupuncture on TST night. Only light therapy was effective in improving SE and SoL, and decreasing the duration of awakenings, although the effects were small.…”
Section: Discussionsupporting
confidence: 91%
“…Only light therapy was effective in improving SE and SoL, and decreasing the duration of awakenings, although the effects were small. Previous meta-analyses [74, 75] and reviews [73, 76] examining light therapy found mixed results regarding TST, SoL, early morning awakening, and daytime sleepiness. In all reviews and meta-analyses, the short-term effects on SE (%) and continuation (WASO) were robust, especially in samples of nursing-home residents with moderate-to-severe dementia [76].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of these new lighting systems coincides with emerging research demonstrating that the spectrum, intensity, distribution, timing, and duration of light can affect task performance, alertness, and sleep patterns (Figueiro, Sahin, et al, 2016;Giménez et al, 2017;Rahman et al, 2017;Smith et al, 2009) and that these effects can be important for healthcare patients (Hadi et al, 2019). The intrinsically photosensitive retinal ganglion cells, with peak sensitivity to short-wavelength light of around 480 nm, help synchronize circadian rhythms and can separately produce short-term alerting effects (Berson et al, 2002;Brainard et al, 2001;Hattar et al, 2002;Lucas et al, 2014;Thapan et al, 2001).…”
mentioning
confidence: 89%
“…A recent review of the emotional, psychological, social, behavioral, and functional antecedents of healing has specifically indicated that creation of a homelike environment, with access to views and nature, appropriate light exposure, noise control, and a room layout that minimizes barriers not only improves patient safety and satisfaction, but also improves recovery, representing the emphasis that evidence based design places on environmental factors (DuBose et al, 2018). More specific explorations of these factors include studying patient exposure to natural and artificial light on sleep quality and subsequent recovery (Hadi et al, 2019), how the design of mental health facilities affects stress and behavior (Connellan et al, 2013;Ulrich et al, 2018), and how perceptions of loneliness diminish recovery from stroke (Anåker et al, 2019). Studies evaluating the effects of acoustics and sound on medical outcomes (Blomkvist et al, 2005;Joseph and Ulrich, 2007;Ulrich, 2008) have also concluded that sound can both help and hinder recovery.…”
Section: Optimization Of Environment In Medicinementioning
confidence: 99%